Assessing social impact in the field of sustainable tourism development: Evidence from Cabo Delgado (MZ). Issue 4 (3rd July 2020) - Castiglioni, Cinzia; Lozza, Edoardo; Anselmi, Paolo; Rossi, Rossella
ABSTRACT: Assessing the social impact of tourism-related activities is of paramount importance to promoting sustainable development. The present study aimed to assess the social impact of a project in Cabo Delgado (MZ), designed to increase local community residents' employability in the emerging tourism sector through the delivery of vocational training programmes, utilising a multi-phase and mixed-method design. The study comprised three different phases (before, during, and after the intervention) and took into account the perspective of a variety of stakeholders. Programmes were perceived to be effective by local operators in the tourism sector and trainees, as they enhanced their living conditions and increased their employability. International operators and tourists, however, had not yet perceived their effectiveness. This study offers a methodological framework for social impact assessment by performing a programme evaluation as an integral part of the intervention itself. This methodology can be extended to other non-tourism related contexts.